The relevancy of blasphemy laws in a plural society: a case study in Malaysia, The United Kingdom and Pakistan / Nur Syazna Ahmad Kamal and Noor Zanariah Haffizah Ghazali - Ahmad Kamal, Nur Syazna; Haffizah Ghazali, Noor Zanariah (2007)
This research mainly touches on the blasphemy laws in three different countries, namely Malaysia, the United Kingdom and Pakistan. Problems such as the setbacks faced in a Christian-dominated country such as the United Kingdom, the abuse and misuse of powers by the authorities in Pakistan, and the vague distinction between apostasy and blasphemy in Malaysia is discussed in this project paper. Blasphemy has a close relation with freedom of speech and expression. Thus, this is also discussed thoroughly. We will later analyses whether blasphemy falls within the perimeters of the concept of freedom of speech and expression. This project paper will also look at how blasphemous statements can cause uproars among the different races in a community. Through this project paper, we have a clear picture of the vagueness of the definition of blasphemy in the Penal Code. Confusion is apparent when it comes to dealing with blasphemy, as the people are still unsure as to the differences between apostasy and blasphemy. The laws that are too rigid as in the likes of Pakistan cannot be taken into account, as they are a pure Islamic state, yet we are not. Malaysia should refine their blasphemy laws by first drawing a distinct line between apostasy and blasphemy. Only then will the citizen be aware of the crime being made and the consequences of it.